Molecular and biochemical effects on metabolism and immunity of Hyriopsis cumingii fed with four different microalgae - Sun, Yu; Guo, Kefan; Yu, Xiaobo; Li, Yanhong; Yao, Weizhi; Wu, Zhengli (Frontiers in Marine Science, 2022)
Hyriopsis cumingii has attracted attention because of its pearl production performance and water purification capacity. Realizing sustainable industrialized culture of H. cumingii or applying it to bivalve biomanipulation for controlling water eutrophication needs urgent studies about the selection of suitable algae and the effects of different microalgae on mussel physiology. To contrast molecular and biochemical effects of high-quality microalgal diets (Chlorella vulgaris, Navicula pelliculosa, and Cyclotella sp.) with toxic Microcystis aeruginosa on metabolism and immune physiology of H. cumingii, levels of related enzymes and genes were analyzed during the 28-day exposure period. Results showed that the Cyclotella sp. diet could significantly (p < 0.05) maintain higher levels of metabolic enzymes (glutamic oxaloacetate transaminase (GOT), glutamic pyruvate transaminase (GPT), pyruvate kinase (PK), and hexokinase (HK)) and genes (CPT1 and LDLR). C. vulgaris and N. pelliculosa treatments significantly (p < 0.05) reduced activities of these metabolic parameters. The M. aeruginosa treatment significantly (p < 0.05) enhanced levels of immune enzymes (alkaline phosphatase (AKP), superoxide dismutase (SOD), and catalase (CAT)) and genes (HcIL-17 and IAP) on day 1 or 7, and there was a significant (p < 0.05) reduction on day 28. Results suggested that Cyclotella sp. was the suitable algae for H. cumingii, followed by C. vulgaris and N. pelliculosa, and toxic algae caused metabolic disorders, immune injury, and poor physiological status. The study has practical significance in the sustainable cultivation of H. cumingii and provides a theoretical basis for bivalve biomanipulation in eutrophic water.